GEOLOGI DAN STUDI FASIES GUNUNGAPI AWU, DAERAH BUNGALAWANG DAN SEKITARNYA, KECAMATAN TAHUNA, KABUPATEN KEPULAUAN SANGIHE, SULAWESI UTARA - Djaya, J.H.M.; Rachmadhan, H.D. (LPPM Universitas PRISMA, 2024)
The Sangihe Islands Regency, North Sulawesi Province, is situated between the Talaud Islands Regency and Biaro Islands Regency. This region hosts several active volcanoes, such as Mount Banua Wuhu and Mount Awu, the latter being the highest point in Tahuna District. This study focuses on the volcanic geology, specifically the facies of Mount Awu, conducted in the Bungalawang area of Tahuna District. The methodology involved field surveys encompassing direct observations of surface geological conditions, followed by laboratory analysis and studies. The identification of volcanic facies was based on geomorphology, volcanic rock stratigraphy, and geological structures. Research findings indicate that the study area falls within the distal facies of Mount Awu. The stratigraphy of the area comprises units such as Volcanic Rock Unit, Tuff Santiago Breccia Insert, Santiago Tuff Insert Breccia, Tuff Manente Breccia Insert, Manente Tuff Insert Breccia, and Alluvial Unit. Geomorphological identification, geological structure analysis, and stratigraphy reveal that the study area constitutes a distal facies located at the foothills of Mount Awu. Geological structure analysis indicates the presence of fractures showing a main stress direction towards N3240E. The geological history of the study area began with the formation of the Volcanic Rock Unit due to the eruption of the ancient Sahendarumang volcano. Subsequently, a series of eruption and deposition events formed distinct stratigraphic units. This research contributes significantly to understanding the geological and geological history of the region. Its findings are applicable in various practical applications, including disaster mitigation and natural resource development. This study also serves as a foundation for further research in the field of geology, particularly Volcanology.